Organizational Management Imbalance from the Qur'anic Perspective - Supodo, Yuli; Sarnoto, Ahmad Zain (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
Modern organizational management, rooted in secular Western paradigms, achieves operational efficiency through classical functions planning, organizing, leading, and controlling yet exhibits spiritual-ethical imbalances manifesting as corruption, bureaucratic pathologies, and commercialization in Islamic education institutions. This library research employs Qur'anic content analysis on 12 thematic verses (QS. Yusuf:47-49; Ali Imran:159; Al-Mujadilah:7) to integrate classical management (Terry, Fayol) with Islamic principles (tauhid, syura, muraqabah), producing a holistic Islamic Management Cycle based on Falah for sustainable success (worldly productivity + spiritual blessing). Findings reveal: (1) tauhid (QS. Adz-Dzariyat:56) transforms organizations into worship ecosystems; (2) systematic integration yields Yusufi planning, maslahah organizing, syura leading, muraqabah controlling; (3) 4-stage Maturity Model (Diagnosis 2025→Falah 2035) with KPIs (accreditation A, taqwa 90%, employability 95%). Visualizations (Tables 1-5, Figures 1-2) provide PTIQ Jakarta's 2025-2035 blueprint, addressing 68% PTKIN governance stagnation. Recommendations target academics (empirical validation), practitioners (Renstra implementation), and policymakers (national curriculum integration), bridging Western theory-Islamic praxis gaps for falah-oriented transformation.